Factor Causes of Stunting in Children in Coastal Areas Health Center Lohia , District Lohia , Muna Regency - Nursam Sarumi; Irna Yuningsar; Rasniah Sarumi (Journal of Health Science and Pharmacy, 2025)
Background: Stunting is a form of chronic nutritional problem that has a significant impact on children’s physical growth and cognitive development. This condition generally occurs as a result of prolonged nutritional deficiencies, particularly during the first 1.000 days of life. Objective: This study aims to examine the various determinant factors contributing to the incidence of stunting among children living in coastal areas, with a specific focus on the working area of the Lohia Community Health Center. Methods: This research employed a Systematic Literature Review (SLR) method with a library research approach, drawing from relevant national scientific journal sources. Results: The findings indicate that the incidence of stunting is influenced by multiple factors, including low maternal knowledge regarding nutrition, poor environmental sanitation, inappropriate feeding practices, and low family socio-economic status. In addition, limited access to healthcare services and prevailing cultural perceptions regarding stunting further exacerbate the problem. Conclusion: Efforts to prevent stunting require a multisectoral and collaborative approach involving government institutions, healthcare providers, community leaders, and families. Such synergy is essential to ensure that interventions are implemented not only in the short term but also in a sustainable manner for long-term impact. Keywords: Stunting, Environmental Sanitation, Parenting Practices, Coastal Areas, Maternal Knowledge, Healthcare Services, Child Nutrition